The Relationship Between Enlarged Perivascular Spaces and Cognitive Function: A Meta-Analysis of Observational Studies - Jie, Wanxin; Lin, Guanghong; Liu, Zhou; Zhou, Haihong; Lin, Lifeng; Liang, Guocong; Ou, Mingqian; Lin, Meijun (Frontiers in Pharmacology, 2020)
Enlarged perivascular spaces (ePVS), visible on magnetic resonance imaging (MRI), are associated with aortic pulse wave changes produced by arterial stiffening. However, the relationship between ePVS and cognition is still unclear. We aimed to benchmark current knowledge of associations between ePVS and cognitive function using a meta-analysis of all available published data. We searched three databases for studies examining enlarged perivascular spaces and cognition, identified 7 studies involving 7,816 participants, plotted multivariate-adjusted odds ratio (OR) and 95% CI and generated summary odds ratio (OR) with a fixed effects model. Enlarged perivascular spaces were related to the risk of impaired cognition (OR = 1.387, 95% CI = 1.198-1.606, I2 = 32.6%) with low heterogeneity. There was publication bias, which could be corrected by trimming and supplementation (OR=1.297, 95% CI= 1.130-1.490).EPVS were associated with impaired cognition and may be a sign of cognitive impairment rather than particular diseases. More studies are required to validate ePVS as a measurable risk marker for cognition using consistent methods to determine a characteristic appearance of ePVS .